8. GAMBARAN HISTOPATOLOGIS PARU ANJING LOKAL (Canis lupus familiaris) YANG MENDERITA ANTRAKOSIS Histopathology of Lung of Local Dog (Canis lupus familiaris) with Anthracosis - Safara Malullana Ulfah (Universitas Syiah Kuala, 2016)
This study aims to determine the histopathology of lung of local dog (Canis lupus familiaris) with anthracosis. The study used 30 dogs with the ages of 2 years sacrificed by strychnine and necropsied to collect the lungs. The anatomycal pathology method was used to examine the presence of dust particles in lungs. The samples then proceed to histopathology using standard microtechnic method and stained with hematoxylin-eosin. Data were analyzed descriptively. The result showed that 10 out of 30 samples were positive pulmonary anthracosis proven by carbon pigment found in septae of alveolar, whereas 20 samples negative anthracosis. Other changes observed were emphysema, congestion, edema, hemorrhage, hyperemia, and fibrosis. In conclusion the percentage of dogs with anthracosis in Banda Aceh City and Aceh Besar is 33.33%. ____________________________________________________________________________________________________________________ Key words: lung histopathology, local dog, anthracosis